FAKTOR PENYEBAB MELONJAKNYA ANGKA PERKAWINAN ANAK DI KALANGAN REMAJA SELAMA PANDEMI COVID-19 - Maika Dian Agustin; Riski Apriliyani (Universitas Islam Negeri Alauddin Makassar, 2022)
The COVID-19 outbreak is included in the category of a pandemic that has claimed the lives of many victims. The existence of a pandemic has an impact on all aspects of life, both in the fields of education, social, economy, religion, and culture. The biggest impact of the pandemic is mental and psychological attacks, these psychological problems not only affect adults, but also children and adolescents. The thing that is also highlighted is the increasing number of child marriages carried out by teenagers. This study aims to determine the factors that cause the increase in child marriage among adolescents during the pandemic. The method used is the library research by taking information and data related to this research. The results of this study indicate that the factors causing child marriage during the pandemic are the occurrence of pregnancies outside of marriage, the individual's own factors, the lack of parental supervision of their children, educational factors, economic factors and the rapid development of technology.